Nursing care for children with autismo (Research, Society and Development, 2020)
Autism Spectrum Disorder (ASD) is a nomenclature used for different simian symbols marked by common characteristics. Approaching children with ASD requires professional health skills, knowledge and individualized care strategy. The work aimed to describe aspects related to nursing care for children with autism. This was an integrative literature review. The articles were used using the following databases: PubMed from the National Library of Medicine, VHL (Virtual Health Library), CINAHL (Cumulative Index of Literature in Nursing and Allied Health) and Scielo (Electronic Scientific Library On-Line). We use the studies available in full texts, published in the years 2015 to 2020, in Portuguese and English. 12 articles were selected to execute the research, all items about primary changes in the early detection of the autistic spectrum, such as attention to common signs and symptoms of disorder, an injury or reduced eye contact, low interest in people, stereotyped movements and difficulty or absence of speech; even care after diagnosis, what are the issues that encourage the child to research through the nursing process and to practice objectivity during care and communication with that child. Therefore, environmental and genetic factors are related to the pathophysiology of disorders, as well as antipsychotics, an alternative complementary medication, which is used to control the clinical manifestations used by professionals and nursing care is fundamental in patient monitoring.